Analysis of Learning Strategies for Slow Learner Students in Primary Schools - Ulfach, Shania; Wakhudin, Wakhudin (UM Purwokerto Press, 2025)
Students slow learning is a student who has ability Study more slow compared to student others marked? with performance Study low , frequent late deliver tasks , and require long time in understand material lesson . Observation beginning show the teacher has not Can apply strategy proper learning? to student slow learning . Children slow study in schools general many things are lacking get attention and motivation from the teacher, due to ability limited child? Study This aiming For analyze strategy proper learning? for student slow study . The subjects of the study included the Principal, Class Teacher and 2 students at the Elementary School Country? 1. The Key Study This use approach qualitative studies case with method data collection observation , interviews , and documentation . Research results show that strategies used by teachers in teach slow learner students include ; 1) teacher strategies in management class through implementation various method student -centered learning and approaches ; 2 ) teacher strategies in treat slow learner students in regular classes with method put slow learner students in the front row , doing rotation with notice condition students ; 3) teacher strategies in give task to slow learner students ; 4) teacher strategies in Motivate slow learner students.